Paku Buwono X : penjaga tradisi pelopor modernitas budaya jawa / HM. Nasruddin Ashory Ch., H. Jeihan Sukamtoro - NASRUDDIN ANSHORIY CH, HM; Jeihan Sukmantoro, H (Ilmu Giri, Jeihan Istitut, 2014)
x, 355 hlm. : ilus. ; 22 cm.